Pengembangan Media 3D Berbasis Augmented Reality Menggunakan PBL Materi Penggolongan Hewan untuk Meningkatkan Self Esteem Siswa Kelas V SD - Kristina; Mohamad Fatih; Cindya Alfi (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2023)
Many media can be used as innovations in learning, and these media can be physical or technological-based. One of the technological-based media is augmented reality-based media. This research aims to determine the process of making 3D media based on augmented reality animal classification material, knowing the validity and feasibility of the media, and find out whether the development of PBL-based augmented reality media animal classification material can increase the self-esteem of grade V students of SD Islam Hasanul Amin, Blitar Regency. The method used in this study is Research and Development (R&D) with research stages of ADDIE model development. The field trial design used is Pre-questionnaire and Post-questionnaire Control Group Design using experimental and control classes. The results of this study obtained the validity and feasibility of 3D media based on augmented reality animal classification material obtained a total value of 88.49%, so this media is very valid / very feasible for use in learning. In addition, it was found that Ho was rejected and Ha was accepted, which means that there are differences in students' self-esteem results by using learning using augmented reality-based media and applying the PBL model, where the self-esteem of students who use augmented reality-based media by applying the PBL learning model is better than students who use conventional learning